A simplified method for predicting the settlement of circular footings on multi-layered geocell-reinforced non-cohesive soils - Moghaddas Tafreshi, S.N.; Shaghaghi, T.; Tavakoli Mehrjardi, Gh.; Dawson, Andrew; Ghadrdan, M. (Elsevier, 2015)
Multiple layers of geosynthetic reinforcement, placed below foundations or in the supporting layers of road pavements, can improve section performance through several mechanisms, leading to reduction in stresses and deformations. This paper aims to present a new analytical solution, based on the theory of multi-layered soil system to estimate the pressure–settlement response of a circular footing resting on such foundations, specifically those containing geocell layers. An analytical model that incorporates the elastic characteristics of soil and reinforcement is developed to predict strain and confining pressure propagated throughout an available multi-layer system, is proposed. A modified elastic method has been used to back-calculate the elastic modulus in terms of strain and confining pressure with materials data extracted from triaxial tests on unreinforced and geocell-reinforced soil samples. The proposed model has been validated by results of plate load tests on unreinforced and geocell-reinforced foundation beds. The comparisons between the results of the plate load tests and proposed analytical method reflected a satisfactory accuracy and consistency, especially at expected, practical, settlement ratios. Furthermore, to have a better assessment of geocell-reinforced foundations' behaviour, a parametric sensitivity has been studied. The results of this study show that the higher bearing pressure and lower settlement were achieved when number of geocell layer, secant modulus of geocell and the modulus number of the soil were increased. These results are in-line with the experimental results of the previous researchers. The study also permits the limits of effective and efficient reinforcement to be determined.